2006
DOI: 10.1111/j.1440-1754.2006.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Is elective surgery traumatic for children and their parents?

Abstract: Mild post-traumatic symptoms may accompany paediatric elective surgery and persist for at least 1 month. Parents may also manifest anxiety and depressive symptoms, which may diminish earlier, that is, immediately after the surgery or within 1 month.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 22 publications
1
40
0
3
Order By: Relevance
“…Confirmando a literatura (Amitay et al, 2006;Broering & Crepaldi, 2011;Moro & Módolo, 2004;Sebastiani & Maia, 2005), a internação para realizar uma cirurgia eletiva caracterizou-se como uma situação estressante para metade das crianças e para 77% dos pais.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Confirmando a literatura (Amitay et al, 2006;Broering & Crepaldi, 2011;Moro & Módolo, 2004;Sebastiani & Maia, 2005), a internação para realizar uma cirurgia eletiva caracterizou-se como uma situação estressante para metade das crianças e para 77% dos pais.…”
Section: Discussionunclassified
“…Mesmo quando se trata de cirurgias eletivas, antes do procedimento, a criança pode experimentar ameaça à sua integridade física, acompanhada do medo da morte e, no pós-cirúrgico, sintomas pós--traumáticos leves que podem se manter por um mês (Amitay et al, 2006).…”
Section: Discussionunclassified
“…For example, Landolt and colleagues [9] reported that 9% of children undergoing hospitalization for a simple, planned surgery (e.g., tonsillectomy) met diagnostic criteria for posttraumatic stress disorder (PTSD) 6-8 weeks following surgery. In a similar study, Ben-Amitay and colleagues [10] documented the occurrence of mild to moderate posttraumatic stress symptoms (PTSS) in 20.5% of children shortly following elective surgeries of various types (e.g., tonsillectomy, adenoidectomy, tendon surgery, etc.). The occurrence of significant levels of distress following an elective procedure suggests that even a planned and relatively routine surgery represents "an event that is out of the ordinary, may be life threatening in [the] case of complications, [and] may lead to pain and disabilities afterwards…" [10, p. 622].…”
Section: Posttraumatic Stress In the Context Of Elective Surgerymentioning
confidence: 96%
“…Na maioria dos casos, a criança é internada e recebe alta no mesmo dia. Amitay et al (2006) mencionam que, embora essas cirurgias sejam planejadas, a criança pode experimentar ameaça à sua integridade física e medo de morrer. Segundo os referidos autores, a retirada de hérnias e da adenóide é comum em crianças e a ansiedade tem sido referida como a resposta emocional mais encontrada.…”
Section: O Estresse De Crianças Submetidas a Procedimentos Cirúrgicosunclassified